Research progress of surgical treatment of rectocele - Zhai Wenjie; Li Mingsen; Li Yuwei; Xu Chen (结直肠肛门外科)
［Abstract］ The primary clinical symptoms of rectocele include difficulty in defecation, pelvic pain, and/or anal swelling, making it a significant contributor to outlet obstruction defecation syndrome. Prolonged difficulty in defecation and associated pain seriously impact the quality of life and mental health of affected individuals. When conservative treatments prove ineffective, surgical intervention is often used to alleviate symptoms and reduce recurrence. Traditionally, surgery involves four main approaches: anus, vagina, perineum, and abdomen. In recent years, advancements in surgical techniques and instruments have led to the evolution of rectocele surgery toward minimally invasive, personalized, and precise procedures. Drawing on the clinical practice of the author’s team and existing literature, this paper reviews surgical methods for rectocele and recent progress in its surgical treatment.